Pelatihan Ketahanan Pangan : Pelatihan Organisme Pengganggu Tanaman (OPT) Tanaman Pisang di Kampung Tumbit Dayak - Sulaminingsih Sulaminingsih; Nurhasyim Nurhasyim; Suwarno Suwarno; Sri Hartini (I-Com: Indonesian Community Journal, 2026)
Banana is a strategic commodity that plays an important role in food security and farmers’ livelihoods; however, its production is threatened by plant pests and diseases (PPD) such as Fusarium wilt and Sigatoka. Farmers’ limited knowledge in recognizing early disease symptoms is the main reason for implementing this community service activity in Tumbit Dayak Village. The implementation method consisted of three stages: preparation, core activities, and evaluation, using interactive lectures, group discussions, demonstrations, and field practice. The results showed an increase in participants’ knowledge, with the average pretest score rising from 55.5 to a post-test score of 80, along with improved observational skills and early detection in the field. Active participation also strengthened the relevance of the material to participants’ practical experience. This activity demonstrates that experience- and practice-based training effectively enhances farmers’ capacity in managing PPD. Therefore, contextual training is a crucial strategy for supporting sustainable banana production and local food security. Keywords: banana, plant pests and diseases, early detection, farmer training, food security